Pengaruh Pola Asuh Orang Tua terhadap Kenakalan Remaja pada Santri Pondok Pesantren Al-Fattah Sukoharjo 2023 - Nuariningsih, Isna; Janah, Daimatul; Muslihudin, Muslihudin (Penerbit Goodwood, 2023)
Purpose: The purpose of this study was to determine the effect of parenting styles on juvenile delinquency that occurred at the Al-Fattah Islamic boarding school, Sukoharjo, in 2023. Methodology: This type of research uses quantitative methods with survey research types. The research instrument was in the form of a questionnaire given to the students of the Al-Fattah Islamic Boarding School. Result: The results of this study indicate that the level of influence of parenting, namely variable X, has an influence on juvenile delinquency, namely variable Y. It is proven from the results of the t test, namely with a significance level of 0.007 <0.05. Limitation: This study has limited research space so that the data obtained and the analysis are more focused on the topics that have been determined. So the limitation of this research is to examine the influence of the parenting style of students at the al-Fattah Sukoharjo Islamic boarding school in 2023. Contribution: This research has many contributions to parents in educating their children and is an academic development for the science of child education.